IMPLIKASI FILSAFAT HEGEL DALAM ETIKA PENDIDIKAN KRISTEN - Laoh, Gerald F. J.; Tanasyah, Yusak; Gumono, Abednego Tri; Putrawan, Bobby Kurnia (Bahasa Indonesia, 2024)
It is undeniable that some philosophical sciences greatly influence Christian education today. In some universities, philosophy is combined with Christian theology and even produces scholars of philosophy of theology. Methods and philosophies of thinking in philosophy are often applied in scientific studies of Christian education today to find an objective truth. In this study, the researcher examines the implications of the thought of a famous modern philosopher, namely George W. F Hegel, on Christian education. Researchers find both in the study of literature that there are several contributions of Hegel's philosophy that have an impact on Christian education today. The religious philosophy of objectivity and subjectivity, the philosophy of process, the philosophy of dialectics, some of Hegel's philosophies found by researchers, have contributed greatly to Christian education today. The philosophies above can be applied by students in teaching education. For example, the implications of dialectical philosophy (thesis, antithesis, and synthesis) on teaching methods of Christian education. These methods and philosophies are often used by Christian education students to teach their students and often create questions and discussions by their students.